Influence of the sulfate content of the exopolysaccharides from Porphyridium sordidum on their elicitor activities on date palm vitroplants - Drira, Marwa (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.